2016
DOI: 10.7717/peerj.2654
|View full text |Cite
|
Sign up to set email alerts
|

Yangtze River, an insignificant genetic boundary in tufted deer (Elaphodus cephalophus): the evidence from a first population genetics study

Abstract: Great rivers were generally looked at as the geographical barrier to gene flow for many taxonomic groups. The Yangtze River is the third largest river in the world, and flows across South China and into the East China Sea. Up until now, few studies have been carried out to evaluate its effect as a geographical barrier. In this study, we attempted to determine the barrier effect of the Yangtze River on the tufted deer (Elaphodus cephalophus) using the molecular ecology approach. Using mitochondrial DNA control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 93 publications
(97 reference statements)
2
20
0
Order By: Relevance
“…In this study, EBSP revealed that O. tormota experienced an effective population size expansion since 0.075 Mya and reached the largest population size around 0.017 Mya; this finding was also supported by the neutral tests, mismatch distribution analysis, and a star‐like network. The demographic expansion of O. tormota during this period is consistent with many species in East Asia, such as the Shangcheng stout salamander ( P. shangchengensis ; Pan et al ., ), Chinese bamboo partridge ( B. thoracica ; Huang et al ., ), Chinese hwamei ( Leucodioptron canorum ) (Li et al ., ), and tufted deer ( Elaphodus cephalophus ) (Sun et al ., ). This phenomenon has also been observed in species from mid‐latitude Europe, such as the Maltese wall lizard ( Podarcis filfolensis ; Salvi et al ., ) and Italian wall lizard ( P. siculus ; Senczuk et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In this study, EBSP revealed that O. tormota experienced an effective population size expansion since 0.075 Mya and reached the largest population size around 0.017 Mya; this finding was also supported by the neutral tests, mismatch distribution analysis, and a star‐like network. The demographic expansion of O. tormota during this period is consistent with many species in East Asia, such as the Shangcheng stout salamander ( P. shangchengensis ; Pan et al ., ), Chinese bamboo partridge ( B. thoracica ; Huang et al ., ), Chinese hwamei ( Leucodioptron canorum ) (Li et al ., ), and tufted deer ( Elaphodus cephalophus ) (Sun et al ., ). This phenomenon has also been observed in species from mid‐latitude Europe, such as the Maltese wall lizard ( Podarcis filfolensis ; Salvi et al ., ) and Italian wall lizard ( P. siculus ; Senczuk et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Compared with the drastic climate oscillations and glacial cycles in Europe and North America (Hewitt, ; Schmitt, ), there was a relatively mild Pleistocene climate and lack of ice sheets in many areas of East Asia (Rost, ; Weaver et al ., ; Ju et al ., ). East Asia has a mosaic of mountains lower than 2000 m. In this area, species generally exhibited two population dynamic patterns in response to Pleistocene climate change: population expansion and contraction for some biological groups (Huang et al ., ; Ding et al ., ; Sun et al ., ), or minor effects on the population demography of other species, such as spiny frogs ( Quasipaa boulengeri ) (Yan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations